The Crime Prevention Program in Barangay 176 Bagong Silang Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crime is a social phenomenon, which means that crime cannot be abolished; it can beregulated by crime prevention initiatives implemented by authorities. Crime is a major problemthat affects everyone in society. It is a problem for today's society that can have long-termconsequences for victims, their families, and communities. The purpose of the study is todetermine the level of crime prevention programs in Barangay 176 Bagong Silang, CaloocanCity, as well as to understand their effect on society in general. It also aims to find out whatprevention is the most effective. Community crime prevention programs or strategies targetchanges in the community, culture, or the physical environment in order to reduce crime in thefuture. This study will also be an eye-opener for barangay officials of barangay 176 BagongSilang Caloocan City, showing that prevention programs are very valuable in preventingcrimes in the future. This study also aims to enhance their ways of how maintaining the peaceand order of their barangay. This would help and add up further details and information thatare useful for our research since this research already has the information they seek,therefore making our research easy.Measures - Rank one, “reducing opportunities for crimes to be committed,” with a total meanscore of 3.68, interpreted as Strongly Agree. Rank two. “Improving the ability of barangaypersonnel,” with a mean score of 3.63, was interpreted as strongly Agreeable. Rank three,“Strategy of barangay for crime prevention,” with a total mean score of 3.55, interpreted asStrongly Agree. Rank four, “Implementing of peace and order in barangay,” with a total meanscore of 3.40, interpreted as Strongly Agree. Rank five, “Increasing surveillance installinglocks and alarms,” with a total mean score of 3.38, interpreted as Strongly Agree. In terms ofindicators above in Barangay Officials, the indicators showed that the “Increasing surveillanceinstalling locks and alarms” with a weighted mean of 3.65 interpreted as Strongly Agree, nextis “Improving the ability of barangay personnel with weighted mean of 3.5 interpreted asStrongly Agree and “Strategy of barangay for crime prevention” with the weighted mean of3.45 interpreted as Strongly Agree and “Reducing opportunities for crimes to be committed”the with weighted mean of 3.40 interpreted as Strongly Agree, lastly, “Implementation ofpeace and order in barangay” with weighted mean of 3.25 interpreted as Agree. In terms ofindicators above in Police Officers, the indicators showed “Reducing opportunities for crimesto be committed” with a weighted mean of 3.95, interpreted as Strongly Agree; next is“Improving the ability of barangay personnel” with a weighted mean of 3.75 interpreted asStrongly Agree and “Implementation of peace and order in barangay” with the weighted meanof 3.70 interpreted as Strongly Agree and “Strategy of barangay for crime prevention” withweighted mean of 3.65 interpreted as Strongly Agree”, lastly, “Increasing surveillanceinstalling locks and alarms” with weighted mean of 3.10 interpreted as Agree.This research would be a great help and give ideas to the government to increase their crimeprevention programs to where they are lacking and give them more ideas. This researchwould help the students be aware of the situation in their communities, especially those in the municipality of Caloocan City. This would help the police department to understand or furtherthe information that could be found in this research. This aimed primarily to determine theeffectiveness of crime prevention strategies implemented by the Philippines National Police(PNP) in terms of police integrated patrol system, barangay peacekeeping operation, anti-criminality operation, and integrated area community public services. Crime preventionstrategies and measures aim to reduce the likelihood of crimes occurring as well as theirpotentially harmful effects on individuals and society, including fear of crimes, by interveningto influence their multiple causes. Barangay response is fundamentally about and forcommunities. As a result, we must always consider the public option when establishing crimeprevention priorities and devising appropriate responses; the promotion of community safetyprocesses in terms of reassurance and barangay response were frequently mentioned asimportant factors with the right response at the right time, the public expected greaterbarangay engagement, which would impact crime and fear of crime. The police are primarilyresponsible for the maintenance of public order. The industry of crime prevention anddetection.
Keywords: Criminology